A 3-piece penile prosthesis salvage in the presence of late-onset infected hematoma: Clinical, radiological and intraoperative findings—A case report. (2019) - Fallatah, Moayid; Bin Mosa, Manerh; Aljuhayman, Ahmed; Alhathal, Naif
Highlights: Penile prosthesis infection is a serious complication often managed radically. In selected patients, infected prosthesis can be salvaged without removal. Wound washout with antimicrobials and antiseptics is a key component of the management. Abstract: Introduction: Erectile dysfunction (ED) is a common health problem affecting 30% of young men worldwide. Despite the availability of non-invasive lines of management, penile prosthesis insertion is considered as a definite solution for ED. Despite strict perioperative measures, infection still complicates around 3% of penile prosthesis surgeries. Presentation of case: This is a case of a 36-year-old male who had an infected scrotal hematoma that led to prosthesis malfunction due to the inability to locate the pump to activate and deactivate the device. Intraoperatively, the prosthesis was salvaged after hematoma evacuation and ensuring a good device functionality. Discussion and conclusion: Infected penile prostheses are usually either removed completely with a new device insertion a few months later or exchanged at the same setting with vigorous wound washout. We suggest salvaging penile implants which are surrounded by infected hematomas in selected patients who don't manifest systemic signs of infection. This approach will help in cost reduction and avoiding further intraoperative complications.